DIVERSIDADE DE PEIXES EM MICROBACIAS DO ALTO RIO PARANÁ, MATO GROSSO DO SUL - NEVES, Gabriela Ribeiro,; CÓRDOVA JÚNIOR, Renner Fernando da Silva,; PINHO, Henrique Ledo Lopes,; MINILLO, Alessandro,; SÚAREZ, Yzel Rondon, (ANAIS DO ENIC, 2024)
-